2019
DOI: 10.35940/ijrte.b1017.0982s919
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning through Duolingo Mobile Application: Teacher Acceptance, Preferred Application Features and Problems

Abstract: Vocabulary learning is vital towards acquiring new languages and therefore insufficient vocabulary knowledge can be considered a significant barrier to such learning. Availability of tools to enhance or simplify the learning process is an added advantage to encourage learners to learn new languages. This research was conducted to investigate teacher acceptance of mobile applications in Saudi Arabian universities for vocabulary learning, identify suitable features for vocabulary learning applications and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The researcher could adjust the questions related to the research topic and was allowed to provide the participants with plenty of time before answering questions. Coding was used to analyze the surveys and interviews; it employed focused and theoretical coding methods (Saldana et al, 2019). The first stage was an overview of the participant's general perception of mobile games in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researcher could adjust the questions related to the research topic and was allowed to provide the participants with plenty of time before answering questions. Coding was used to analyze the surveys and interviews; it employed focused and theoretical coding methods (Saldana et al, 2019). The first stage was an overview of the participant's general perception of mobile games in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Vocabulary plays an important role in language learning. It is the core component of language proficiency and provides much of the basis for how well learners speak, listen, read, and write (T. R. Abdulrahman & Basalama, 2019;Abrar et al, 2018;Nguyen & Khuat, 2003;Saldana et al, 2019). According to Cameron (2001) vocabulary knowledge is the knowledge of knowing second language words.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the teachers considered mobile applications as practical tools to enhance collaboration between learners, exchange knowledge and lesson activities, and assist each other regarding the technical issues they encounter. Alsaif and Farhana (2019) explored EFL teachers' acceptance of MALL applications in learning vocabulary, particularly Duolingo. The participants were 20 Saudi EFL teachers who responded to a questionnaire, and only three were interviewed.…”
Section: Efl Teachers' Perspectives On the Roles Of Edutainment In Te...mentioning
confidence: 99%
“…Although extensive research has been carried out on using technology to support vocabulary learning, a considerable literature has grown up around the theme of edutainment, in particular, in teaching and learning vocabulary, regarding learners' cognitive development, psychology, and social behavior (Abdalla, 2015;Bataineh, 2014;Čepon, 2013;Habbash, 2015;Kabooha & Elyas, 2018). However, few Saudi studies (Al-Johali, 2019; Alsaif & Farhana, 2019;Kabooha & Elyas, 2018) have investigated teachers' perspectives on teaching vocabulary in enjoyable learning environments. Therefore, this quantitative study's primary goal is to explore university EFL instructors' perspectives on the roles of edutainment in teaching vocabulary in Saudi Arabia concerning learners' cognitive, psychological, and social development.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation